Paracoccidioidomycosis in the Central Nervous System - Mesquita Filho, Paulo Moacir; Hofmann, Agatha; De Carli, Fernanda; Araújo, Moisés Augusto; Giacomelli, Richard; Manfroi, Gregori; Leal, Elizabeth; Isbert, Bruna Bley Mattar; Schwingel, Daniela (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2016)
Paracoccidioidomycosis is a systemic mycosis caused by the Paracoccidioides brasiliensis fungus, which is endemic in Latin America. Brazil is the country with the highest number of cases. The affection of the central nervous system (CNS), a potentially fatal condition, occurs in ∼ 12% of the cases. The following forms of presentation are identified: meningeal, which is unusual; meningoencephalitic; and pseudotumoral, the latter two being more frequent. Imaging tests are essential for the diagnosis, but the histological identification of the fungus is required for confirmation of the pathology. The clinical picture depends on the neuraxial location. We present a case of a male rural worker, with expansive lesions in the CNS compatible with paracoccidioidomycosis.
Keywords: neuroparacoccidioidomycosis; paracoccidioidomycosis; fungal abscess